Modele internetowe a wsparcie klienta w procesie zakupu ubezpieczenia - Kaczała, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The purpose of the article is to consider how the application of b2c type internet models (business-to-customer) in an insurance distribution channel supports the client in the process of buying insurance services. The solution to this problem has been based on the theory of information. It is assumed that going from one stage of the buying process to the other requires the insured to have a minimum knowledge he can be certain of enough. The article points at the cost of acquiring this knowledge through the traditional channels and through the internet. The considerations led to some practical conclusions regarding the modes of use of the internet-based distribution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 242-251